Encyclopedia of organizational knowledge, administration, and technology - Khosrow-Pour, Mehdi, 1951- (Advances in logistics, operations, and management science (ALOMS) book series., 2021)
"This book explores the latest concepts, issues, challenges, innovations, and opportunities covering all aspects of modern organizations. Moreover, it is comprised of content that highlights major breakthroughs, discoveries, and authoritative research results as they pertain to all aspects of organizational growth and development including methodologies that can help companies thrive and analytical tools that assess an organization's internal health and performance"--